THE DIFFERENCE IN THE EFFECT OF RED GUAVA JUICE AND PAPAYA JUICE ON HEMOGLOBIN LEVELS IN ADOLESCENT GIRLS AT SMAN 1 PRAYA BARAT USING A HEMOGLOBINOMETER - Suhartiningsih; Endah Sulistiyani Parida; Nia Firdianty Dwiatmojo Parida (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2025)
Background: Anemia among adolescent girls in Indonesia presents a concerning issue. The prevalence of anemia among adolescent girls in West Nusa Tenggara (NTB) is 48%, in Central Lombok Regency it is 1,820 cases, and at SMAN 1 Praya Barat, 53 out of 419 female students were affected in 2024. To address the anemia cases, the Ministry of Health of West Nusa Tenggara has implemented a program providing iron supplements to adolescent girls. In line with this ministry program, this research is crucial as one of the solutions to reduce anemia cases. Objective: To determine the difference in the effectiveness of red guava juice and papaya juice in increasing hemoglobin levels among adolescent girls at SMAN 1 Praya Barat. Method: This study is a quantitative research with a comparative experimental approach, using purposive sampling technique. The measurement tool used is a hemoglobinometer, and the experiment employs an independent t-test data analysis with a sample of 30 respondents. Results and Discussion: The research results show that red guava juice has an average increase of 2.38, while papaya juice has an increase of 1.35. Data analysis revealed that the mean hemoglobin level for red guava juice was 12.92, while the mean for papaya juice was 11.99. This indicates that red guava juice is more effective in increasing hemoglobin levels in adolescent girls at SMAN 1 Praya Barat compared to papaya juice. Conclusion: The conclusion of this study is that red guava juice is more effective than papaya juice in increasing hemoglobin levels among adolescent girls at SMAN 1 Praya Barat.